1998
DOI: 10.2527/1998.7692444x
|View full text |Cite
|
Sign up to set email alerts
|

Interactive effects of betaine, crude protein, and net energy in finishing pigs.

Abstract: Two experiments were conducted to determine the effect of betaine on growth and carcass characteristics of finishing pigs. In Exp. 1, 32 gilts were fed one of two diets: 1) a corn-soybean meal basal (B) diet or 2) B + .125% betaine diet. In Exp. 2, 122 gilts were allotted to one of eight dietary treatments in a 2 x 2 x 2 factorial arrangement with two levels of betaine (0 or .125%), crude protein (adequate [ACP] or inadequate [ICP]), and net energy (NE; 0 or 6% added fat). In Exp. 1, betaine did not affect (P … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

18
73
4
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(96 citation statements)
references
References 0 publications
18
73
4
1
Order By: Relevance
“…Our data indicated that betaine and betaine 1 CLA supplementation did significantly decrease serum urea concentration compared with Control pigs, suggesting dissimilar protein metabolism. Similar results were also reported in finishing pigs (Matthews et al, 1998;Huang et al, 2007) fed betaine. On the contrary, Martins et al (2010) in Alentejano finishing pigs reported no effect of betaine on plasma urea.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Our data indicated that betaine and betaine 1 CLA supplementation did significantly decrease serum urea concentration compared with Control pigs, suggesting dissimilar protein metabolism. Similar results were also reported in finishing pigs (Matthews et al, 1998;Huang et al, 2007) fed betaine. On the contrary, Martins et al (2010) in Alentejano finishing pigs reported no effect of betaine on plasma urea.…”
Section: Discussionsupporting
confidence: 89%
“…However, contrary to Ostrowska et al (2002), we have found no serum NEFA change in pigs fed CLA diets and similar results were found in lactating sows (Bontempo et al, 2004). In this study, betaine had no effect in serum NEFA and similar results have previously been reported (Matthews et al, 1998;Øverland et al, 1999). Furthermore, it is interesting to point out that whole body or hepatic fatty acid oxidation was not affected by betaine in growing pigs (Wray-Cahen et al, 2004), suggesting that reduction in adipose accretion must be via a mechanism other than oxidation.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…While most studies examining betaine supplementation have been with poultry and pigs, its effects are equivocal in other species where the responses are less obvious (Bock et al 2002;Fernández et al 1998;Loest et al 2002). In pigs, the varied responses to betaine are thought to be due to the protein and energy content of the diet (Matthews et al 1998) and this may also be the case in cattle. There is little uniformity between studies, deeming the interpretation of pooled responses to betaine in cattle impractical; however, the effect of betaine on lipid metabolism is a recurring theme.…”
Section: Discussionmentioning
confidence: 99%